Physicochemical softening of a bituminous binder by a reactive surfactant (dodecenyl succinic anhydride, DSA). (20th October 2019) - Ortega, Francisco J.; Navarro, Francisco J.; Jasso, Martin; Zanzotto, Ludo
Graphical abstract: Highlights: A novel physicochemical rejuvenator is proposed. DSA reacts with polar compounds in bitumen, modifying its colloidal stability. DSA can be used as an effective bitumen rejuvenator. DSA improves adhesion and offers better wettability of a siliceous aggregate. Abstract: The development of recycling technologies of asphalt pavements has encouraged industry to promote the use of modifying agents (rejuvenators and/or softeners) able to soften aged bitumen. In this paper, a new concept of physicochemical rejuvenation is described, by using a reactive surfactant (dodecenyl succinic anhydride, DSA). The results obtained demonstrate that DSA addition makes a binder less stiff and viscous in the entire in-service temperature range, being more effective than a selected benchmark: engine oil. Rheological techniques also point to a notable improvement at low temperature, as modification by DSA shifts the glassy regions of the mechanical spectrum towards lower temperatures, decreasing the flexural creep stiffness and increasing the rate of creep, hence yielding binders that can withstand higher stress before cracking failure. Unlike most of rejuvenators used, which merely act as physical softeners by diluting bituminous binders with oils, FTIR data evidence the existence of chemical interactions, hinting at the attachment of DSA to polar compounds in bitumen. These new chemical species affect the degree of association and dispersion of such polar constituents, modifying the colloidal stability, which gives rise to the observed rheological behaviour. Finally, contact angle measurements show an improvement in binder wettability of a siliceous aggregate.